2010
DOI: 10.3748/wjg.v16.i37.4677
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic adenovirus SG600-IL24 selectively kills hepatocellular carcinoma cell lines

Abstract: SG600-IL24 can selectively suppress the proliferation and apoptosis of HCC cell lines in vitro but not normal liver cell line L02 in a p53-independent manner. Compared with Ad.IL-24, SG600-IL24 can significantly enhance the antitumor activity in HCC cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Importantly, p63 and p73 isoforms were not sufficient to compromise Adp53sensor replication, demonstrating that this approach was not restricted by other p53 family members in HCC cells [111]. Thus, novel virotherapeutic strategies based on p53 integrity may overcome limitations of previous oncolytic approaches and some studies suggested that HCC cells are promising targets [112,113].…”
Section: Gene Therapeutic Approachesmentioning
confidence: 93%
“…Importantly, p63 and p73 isoforms were not sufficient to compromise Adp53sensor replication, demonstrating that this approach was not restricted by other p53 family members in HCC cells [111]. Thus, novel virotherapeutic strategies based on p53 integrity may overcome limitations of previous oncolytic approaches and some studies suggested that HCC cells are promising targets [112,113].…”
Section: Gene Therapeutic Approachesmentioning
confidence: 93%
“…Recently, a number of scientific reports have described oncolytic Ads armed with the mda-7 /IL-24 gene, for example, SG600-IL24, an oncolytic Ad harboring mda-7 /IL-24 selectively induces apoptosis in different hepatocarcinoma cell lines without affecting a normal liver cell line (Xue et al, 2010). In another approach, an E1B-55K d deleted oncolytic Ad car rying mda-7 /IL-24 was developed (ZD-55-IL-24) that exhibited better therapeutic efficacy compared with ONXY-015 against hepatic cancer (Xiao et al, 2010).…”
Section: Cancer Terminator Viruses: Efficacious Reagents For Cancementioning
confidence: 99%
“…Second, adenovirus type 5 specifically binds to hepatocytes via coagulation factor X and heparin sulfate proteoglycans [25]. Replication-competent oncolytic adenovirus SG600-IL-24 has the telomerase reverse transcriptase promoter (TERTp) and the hypoxia regulatory elements (HRE) controlling the expression of adenoviral mutated E1a gene and the E1b, respectively [26-28]. Mutation of the E1a gene and its expression driven by the telomerase promoter hinders its replication in normal cells but not in tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore SG600-IL-24 has enhanced effectiveness and safety for cancer gene therapy. We have recently shown that SG600-IL-24 inhibits growth and increases apoptosis of several HCC cell lines in vitro [27,28]. The in vitro anti-tumor activity of oncolytic adenovirus SG600-IL-24 was significantly greater than that of replication defective adenovirus IL-24 [27].…”
Section: Introductionmentioning
confidence: 99%